Некоторые морфометрические закономерности в повышении продуктивности животных - Шпет, Г.И. (Вестник зоологии, 1975)
Body roundness is pronounced in a general course of evolutionary development of animals characterizing an increase in their productivity. This is illustrated by numerous examples on various groups of vertebrates and invertebrates. In this connecteon the co- efficient of roundness (C,) is suggested for introduction. An increase in productivity gives advantages to corresponding animals in the struggle for existence in the course of further evolution. C, may be also an index in the work of a breeder. Possible explanation of the described regularity is presented.